Racial violence and the Brexit state - Jon Burnett (Race & Class, 2017)
Research by the Institute of Race Relations, into over one hundred incidents of racial violence reported in the mainstream media in the month after the 2016 EU referendum, indicates that the ‘spike’ in such attacks has to be understood in terms of the climate created not just during the referendum debate, but also in the policies and programmes of successive governments preceding it. Political figures and senior criminal justice system personnel, who have recently condemned the violence, analyse it in terms of already given media frameworks about ‘hate crime’: bigoted individuals are to blame; this is a law-and-order issue not a socially based problem and so on – thus avoiding any responsibility for legitimising racist violence. The research also reveals the central role of the police, at the expense of community groups’ or victims’ voices, in defining when and what racist violence is deemed newsworthy.